The diet of two opportunistic seabirds (Caspian and Royal Terns) confirms the importance of Sardinella spp. in West African coastal food webs. Issue 9 (26th November 2018) - Correia, Edna; Granadeiro, José Pedro; Regalla, Aissa; Monteiro, Hamilton; Catry, Paulo
ABSTRACT : Despite their importance for fisheries, livelihoods and biodiversity conservation, shelf ecosystems in West Africa are poorly known. Caspian Tern ( Hydroprogne caspia ) and Royal Tern ( Thalasseus maximus ) are two of the most numerous and widespread nesting seabirds in the region, and an understanding of the diet of these opportunistic predators may throw light on important elements of the local food webs. This study describes and compares the prey consumed by these two species in Guinea and Guinea-Bissau collected from 2013 to 2015. Our results show that both tern species feed mostly on pelagic fish from which Clupeidae (mostly Sardinella maderensis ) dominated the diet at all locations and seasons. Pristigasteridae and Polynemidae were the next most frequent prey in the diet of these two tern species. Our findings strengthen the recent suggestion of a wasp-waist ecosystem for our study area, with sardinella as the key prey for several predators, including seabirds and pelagic fishes, and potentially influencing their distribution and abundance. Moreover, our results show a higher diversity in the diet of the Caspian Tern, with this species preying on a greater range of benthopelagic fishes (e.g. Gerreidae; Mugilidae) which fits with observations of inshore foraging that seems rarer in Royal Terns. We further show that prey identification based only on otoliths from pellets, as opposed to the use of all hard structures (e.g. otoliths, vertebrae, scales), seriously underestimates the occurrence of species with fragile and small otoliths, including clupeids and other small pelagics.